Cerritos como patrimônio arqueológico: o resgate do sítio arqueológico corredor do bolso - Marion, Ricardo Pellegrin (2010)
This paper presents the current research in the Archaeological Site Corredor do Bolso, located at Santa Margarida do Sul munipality, Rio Grande do Sul state, Brasil. The site, excavated in 1998, was impacted by agricultural activities, but still preserved two partially intact mound structures, known in the literature as Cerritos . The studied collection is composed of chipped lithic artifacts from various raw materials and ceramic fragments. The diversity of raw materials used in chipping reflects the various geological formations of the region and the mobility of prehistoric groups for resources acquisition. The study of material culture shows the occurrence of two distinct prehistoric occupations: a hunter-gatherer group s occupation, responsible for the construction of Cerritos and a posterior Guarani horticulturalists groups. Thus, attempted to interpret the chipped materials lithic linked to the huntergatherers group and their insertion into the archaeological context in an attempt to understand the construction of Cerritos. And finally, connect these data with the Guarani occupation.